The economics of philanthropy : donations and fundraising - Scharf, Kimberly A. 1961-; Tonin, Mirco, 1976- (The MIT Press, 2018)
Experts bring economic tools to bear on philanthropic activities, addressing topics that range from the determinants of giving to the effectiveness of fundraising techniques. Economists are increasingly aware of the need to better understand philanthropic activities. In this book, economists address a variety of topics related to the economics of philanthropy, ranging from the determinants of giving to the effectiveness of fundraising techniques. The contributions focus on individual motives for giving and volunteering, and in particular how they affect donation outcomes, fundraising decisions, and public policies toward giving. Previous research has viewed motives for giving as embedded in formal models of economic behavior with rational agents who maximize their own utility while constrained by a budget. These models, however, have been shown to have poor predictive power, neglecting direct and indirect motives for giving. The contributors consider, among other subjects, the free-riding problem in these models; altruistic, direct, and indirect motives for giving, addressed both theoretically and with lab experiments; the linear public good game; the role of social information; the effectiveness of matching gifts and premiums; motives for unpaid volunteering; subscription models as a way to regulate revenue streams; and increasing reliance on public funds. - Resumé vydavatel
Keywords: charitativní organizace; fundraising; dárcovství; charitable organizations; fund raising; generosity; elektronické knihy; sborníky; electronic books; papers of several authors